Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper applies a range of methods to assess Italy's competitiveness gap versus other euro area members. All indicators point to a clear erosion of competitiveness in recent years, with related market share losses. Nonetheless, the estimated competitiveness gap, while appreciable, still remains quantitatively contained. The results suggest that the unwinding of the competitiveness gap will require reforms that boost productivity growth and continued wage moderation, as well as an adjustment by export firms in Italy.